Individual differences in parasympathetic nervous system reactivity in response to everyday stress are associated with momentary emotional exhaustion - Regina Franziska Schmid; Joachim Thomas; Katrin Rentzsch (Scientific Reports)
Abstract Acute stressors (e.g., time pressure) can provoke psychological and physiological stress responses, and the magnitude of such responses is called stress reactivity. However, stress reactivity levels can differ considerably among individuals, with exaggerated levels being associated with adverse outcomes (e.g., emotional exhaustion). Previous studies have primarily investigated psychological stress reactivity or physiological stress reactivity induced in the laboratory. Physiological stress reactivity, especially concerning heart rate variability (HRV), has rarely been examined so far in real life. We addressed this research gap in a sample of 394 adults who participated in 2- to 4-day ecological momentary assessments. Individuals answered self-reports on perceived time pressure and emotional exhaustion multiple times a day and simultaneously wore electrocardiogram sensors. Based on 4,009 total situations and 3–16 situations per participant, individual differences in HRV reactivity to time pressure were computed as random slopes from multilevel models. Consistent with preregistered hypotheses, increased time pressure was associated with reduced HRV, and increased stress reactivity was associated with increased emotional exhaustion. The findings highlight the detrimental effects of everyday demands and physiological reactivity and emphasize the relevance of practical coping strategies. This study contributes to research on dynamic inter- and intraindividual stress regulation using ambulatory, psychophysiological methods.